Numerical simulation of high frequency electromagnetic wave in microwave cavity for soot oxidation - Al-Wakeel, H.B. (2013)
Soot oxidation temperature by high frequency electromagnetic energy was proposed using numerical simulation by combining electromagnetic with transient thermal analyses. Equation of electric field distribution in a microwave cavity with perfect electric conductor surfaces and TE10 mode is formulated from Helmholtz equation. The dissipated heat distribution is calculated from the electric field distribution. Six study cases for electric field and dissipated heat distributions were implemented by using ANSYS software based on finite element method. The impact of dielectric sample properties, position, size and shape inside the microwave cavity were predicted. The results from the simulation of electric field and dissipated heat were compared with available data in literature and showed the validity of the analysis. It was found that the electric field forming hot spots at penetration depth and front corners of the soot sample and penetration depth is equal to 12mm but equal to 0 for samples with dimensions less than penetration depth. Dissipated heat pattern depend on electric field pattern and dielectric properties. Â© (2014) Trans Tech Publications, Switzerland.